2018
DOI: 10.1128/mcb.00654-17
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cholesterol Sulfotransferase SULT2B1b by Hepatocyte Nuclear Factor 4α Constitutes a Negative Feedback Control of Hepatic Gluconeogenesis

Abstract: The cholesterol sulfotransferase SULT2B1b converts cholesterol to cholesterol sulfate (CS). We previously reported that SULT2B1b inhibits hepatic gluconeogenesis by antagonizing the gluconeogenic activity of hepatocyte nuclear factor 4α (HNF4α). In this study, we showed that the SULT2B1b gene is a transcriptional target of HNF4α, which led to our hypothesis that the induction of SULT2B1b by HNF4α represents a negative feedback to limit the gluconeogenic activity of HNF4α. Indeed, downregulation of Sult2B1b enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Overexpression of Hnf4a Induces Sult2B1b and Sensitizes Mice or Primary Hepatocytes to APAP-Induced Injury. We recently reported that Sult2B1b is a transcriptional target of Hnf4a (Bi et al, 2018). Having shown that overexpression of SULT2B1b sufficed to sensitize mice to APAP-induced liver injury, we wanted to determine whether upregulation of Sult2B1b by HNF4a in the mouse liver will have a similar sensitizing effect on APAP-induced liver injury.…”
Section: Sult2b1b Sensitizes Mice To Apap Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of Hnf4a Induces Sult2B1b and Sensitizes Mice or Primary Hepatocytes to APAP-Induced Injury. We recently reported that Sult2B1b is a transcriptional target of Hnf4a (Bi et al, 2018). Having shown that overexpression of SULT2B1b sufficed to sensitize mice to APAP-induced liver injury, we wanted to determine whether upregulation of Sult2B1b by HNF4a in the mouse liver will have a similar sensitizing effect on APAP-induced liver injury.…”
Section: Sult2b1b Sensitizes Mice To Apap Toxicitymentioning
confidence: 99%
“…Mechanistically, SULT2B1b and its enzymatic product cholesterol sulfate suppress gluconeogenesis by inhibiting acetyl-CoA synthetase gene expression, leading to reduced acetylation and nuclear exclusion of HNF4a (Shi et al, 2014). More recently, we reported that the SULT2B1b itself is a transcriptional target gene of HNF4a (Bi et al, 2018). The establishment of SULT2B1b as a HNF4a target gene called up our hypothesis that the induction of SULT2B1b by HNF4a involves in a negative feedback to inhibit the gluconeogenic activity of HNF4a (Bi et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Subsequently, some experimental studies also confirmed the above result and further found that the level of cholesterol was positively associated with the malignant degree of cancer cells [16,17]. However, the cholesterol levels in advanced biological cells are maintained in a fairly narrow range, and the negative feedback regulation of endogenous cholesterol synthesis play an important role in maintaining the cholesterol metabolic balance [18,19]. And the biological effect of serum cholesterol was related with low-density lipoprotein (LDL) [20].…”
Section: Discussionmentioning
confidence: 73%
“…The activity of both sulfotransferases and sulfatases regulates signalling via nuclear hormone receptors (NHR), by adding or removing a sulfate moiety to hormones, or their precursors (reviewed by He et al, 25 ). Inversely, NHRs are able to modulate the expression of genes encoding these enzymes, through negative feedback loops operated by their enzymatic products 26 . Interestingly, Burton and co-workers showed that the C. elegans sulfotransferase SSU-1 controls hormonal signalling through NHR-1 to regulate insulin sensitivity and specificity 27 .…”
Section: The Nuclear Hormone Receptor Nhr-1 Modulates Protein Homeostmentioning
confidence: 99%